Multiple Regulatory Levels Shape Autophagy Activity in Plants - Yang, Mingkang; Bu, Fan; Huang, Wei; Chen, Liang (Frontiers in Plant Science, 2019)
Autophagy is a strictly regulated pathway involving the degradation of cytoplasmic organelles and proteins. Most autophagy-related genes have been identified in plants based on sequence similarity to homologues in yeast and mammals. In addition, the molecular mechanisms underlying plant autophagy have been extensively studied in the last decade. Plant autophagy plays an important role in various stress responses, pathogen defense, and developmental processes such as seed germination, pollen maturation, and leaf senescence. However, the regulatory mechanisms of autophagy in plants remain poorly understood. Recent studies have identified several plant autophagy regulators, which modify autophagy activity at transcriptional, post-transcriptional, and post-translational levels. In this review, we summarize recent advances in understanding regarding regulatory network of plant autophagy and future directions in autophagy research.